Permanent facial paralysis: surgical correction with Labbe’s technique - Yangali, Rubén (2008)
Facial paralysis causes a large aesthetic and functional defect. Different surgical techniques may be used to repair this defect. Some of them have focused in structural and physiological aspects. We consider that temporalis lengthening myoplasty is currently the most important technique for permanent facial paralysis repair.